ACTIVITY OF THE TEACHER BASED ON EDUCATIONAL TECHNOLOGIES. - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
In this article, the teacher makes the lesson interesting and enjoyable based on various technologies. And to increase students' interest in science during the lesson.